Synthesis and vibrational spectral (FT-IR, FT-Raman) studies, NLO properties & NBO analysis of (E)-N’(thiophen-2yl methylene)isonicotinohydrazide using quantum chemical method - A, Nathiya; H, Saleem; Bharani, Bharanidharan; M, Suresh (International Journal of Advanced Chemistry, 2018)
FT-IR (4000-400 cm-1) and FT-Raman (3500-50 cm-1) spectra of (E)-N’(thiophen-2yl methylene)isonicotinohydrazide (TMINH) molecule was recorded in solid phase. The optimized geometry was calculated by B3LYP method with 6-311++G(d,p) basis set. The harmonic vibrational frequencies, infrared (IR) intensities and Raman scattering activities of the title compound were performed at same level of theory. The complete vibrational assignments were performed on the basis of the Total energy distribution (TED) of the vibrational modes, calculated with scaled quantum mechanical (SQM) method. The calculated first hyperpolarizability may be attractive for further studies on non-linear optical (NLO) properties of material. Stability of the molecule arising from hyperconjugative interaction and charge delocalization was analyzed using natural bond orbital (NBO) analysis. Highest occupied molecular orbital-Lowest unoccupied molecular orbital (HOMO-LUMO) energy gap explains the eventual charge transfer interactions taking place within the title molecule. A study on the electronic properties, such as excitation energies and wavelengths, were performed by time-dependent (TD-DFT) approach. Molecular electrostatic potential (MEP) provides the information on the electrophilic, nucleophilic and free radical prone reactive sites of the molecule. The thermodynamic properties such as heat capacity, entropy and enthalpy of the title compound were calculated at different temperatures in gas phase. 1H and 13C-NMR chemical shifts of the molecule were calculated using Gauge-independent atomic orbital (GIAO) method.To establish information about the interactions between human cytochrome protein and this novel compound theoretically, docking studies were carried out using SchrÃ¶dinger software.